Development of potential solar induced ventilation strategy in hot and humid climate - Sapian, Abdul Razak; Mohammad Yusoff, Wardah Fatimah; Adam, Nor Mariah; Salleh, Elias (2012)

(untitled)
The use of solar energy in solar induced ventilation helps to enhance the stack ventilation which is normally less efficient in the hot humid climate due to the small temperature difference between the inside and outside of naturally-ventilated buildings. This research aims to examine a potential solar induced ventilation strategy for the hot humid climate. There are two methods used which are the documents survey and a physical test. The documents survey was executed on Trombe wall, solar chimney and roof solar collector. This survey resulted in the proposed development of combined roof solar collector and vertical stack as the most appropriate strategy. A testing using physical model was executed in the actual environmental conditions. The findings indicate that the proposed strategy attained air temperature difference (Ti-To) of 8.5 ºC for 633 W/m² solar radiation. This air temperature difference is more than the usual air temperature difference between the inside and outside of naturally ventilated buildings in Malaysia. Hence, the research concludes that the proposed strategy is able to enhance stack effect ventilation in hot and humid climate.